Baseline characteristics of study sites and women enrolled in a three-arm cluster randomized controlled trial: PMTCT uptake and retention (pure) Malawi - Monique van Lettow; Hannock Tweya; Nora E. Rosenberg; Clement Trapence; Virginia Kayoyo; Florence Kasende; Blessings Kaunda; Mina C. Hosseinipour; Michael Eliya; Fabian Cataldo; Salem Gugsa; Sam Phiri; et al. (BMC, 2017)
Abstract Background Malawi introduced an ambitious public health program known as "Option B+" which provides all HIV-infected pregnant and breastfeeding women with lifelong combination antiretroviral therapy, regardless of WHO clinical stage or CD4 cell count. The PMTCT Uptake and REtention (PURE) study aimed at evaluating the effect of peer-support on care-seeking and retention in care. Methods/design PURE Malawi was a three-arm cluster randomized controlled trial that compared facility-based and community-based models of peer support to standard of care under Option B+ strategy. Each arm was expected to enroll a minimum of 360 women with a total minimum sample size of 1080 participants. 21 sites (clusters) were selected for inclusion in the study. This paper describes the site selection, recruitment, enrollment process and baseline characteristics of study sites and women enrolled in the trial. Results Study implementation was managed by 3 partner organizations; each responsible for 7 study sites. The trial was conducted in the South East, South West, and Central West zones of Malawi, the zones where the implementing partners operate. Study sites included 2 district hospitals, 2 mission hospitals, 2 rural hospitals, 13 health centers and 1 private clinic. Enrollment occurred from November 2013 to November 2014, over a median period of 31 weeks (range 17-51) by site. A total of 1269 HIV-infected pregnant (1094) and breastfeeding (175) women, who were eligible to initiate ART under Option B+, were enrolled. Each site reached or surpassed the minimum sample size. Comparing the number of women enrolled versus antenatal cohort reports, sites recruited a median of 90% (IQR 75-100) of eligible reported women. In the majority of sites the ratio of pregnant and lactating women enrolled in the study was similar to the ratio of reported pregnant and lactating women starting ART in the same sites. The median age of all women was 27 (IQR 22-31) years. All women have ≥20 months of possible follow-up time; 96% ≥ 2 years (24-32 months). Conclusion The PURE Malawi study showed that 3 implementing partner organizations could successfully recruit a complex cohort of pregnant and lactating women across 3 geographical zones in Malawi within a reasonable timeline. Trial registration This study is registered at clinicaltrials.gov - ID Number NCT02005835 . Registered 4 December, 2013.